Attitude of Syrian students toward GAD patients: An online cross-sectional study - Swed, Sarya; Shoib, Sheikh; Khan, Ubaid; El-Sakka, Amro A.; Almoshantaf, Mohammad Badr; Hassan, Noheir Ashraf Ibrahem Fathy; Khairy, Lina Taha; Bakkour, Agyad; Muwaili, Ali Hadi Hussein; Motawea, Karam R.; Abdelmajid, Fatima Abubaker Abdalla; Mohammed Sharif Ahmad, Eman; et al. (Frontiers in Public Health, 2022)
Generalized Anxiety Disorder (GAD) is a prevalent condition and a significant cause of mental disability and poor quality of life. People with GAD have chronic worrying, restlessness, and discrimination from the general public; Little is known about the stigmatizing attitudes toward people with GAD among Syrian students. The questionnaires contained demographic data about age, gender, social status, personal stigma toward GAD scale, perceived stigma toward GAD scale, social distance with those with GAD, the participants' usual source of their knowledge about GAD, helpful interventions, and supporting information. A total of 1,370 replies were collected, but only 1,358 were used for analysis as 12 participants declined to complete the survey. About 44.1% of participants agreed that people with GAD could snap out of the problem, most of them being females (32.4% of the total population). Compared to medical students, more non-medical students (7.1% of the total population) believed that anxiety is a sign of personal weakness. This study demonstrated that Syrian college students showed a high level of stigmatizing and socially distancing attitudes toward people with GAD, particularly female and non-medical students.